Biocatalytic preparation of acylated derivatives of flavonoid glycosides enhances their antioxidant and antimicrobial activity - Mellou, F.; Lazari, D.; Skaltsa, H.; Tselepis, A. D.; Kolisis, E.; Stamatis, H. (2005)
Enzymatic synthesis of acylated derivatives of a monosaccharidic flavonoid chrysoeriol-7-O-beta-D-(3"-E-p-coumaroyl)glucopyranoside as well as of a disaccharidic flavonoid chrysoeriol-7-[6'"-O-acetyl-beta-D-allosyl-(1 --> 2)-beta-D-glucopyranoside], isolated from Greek endemic plants, was performed using an immobilized Candida antarctica lipase in non-toxic organic solvents. The influence of the reaction parameters such as the molar ratio of acyl donor to flavonoid, as well as the nature of the acyl donor, on the performance of the biocatalytic process was pointed out using the acylation of naringin as a model reaction. With vinyl laurate as acyl donor, the highest conversion was observed at relatively high molar ratio (greater than or equal to 10), using acetone as solvent. Lipase exhibits specificity towards primary alcohol of the glucose moiety of both flavonoid glycosides. The introduction of an acyl group into glucosylated flavonoids significantly improved their antioxidant activity towards both LDL and serum model in vitro. Furthermore, the acylated derivative of disaccharidic flavonoid increased its antimicrobial activity against two Gram-positive bacteria. (C) 2004 Elsevier B.V. All rights reserved. Journal of Biotechnology